2011
DOI: 10.1007/s00520-011-1316-4
|View full text |Cite
|
Sign up to set email alerts
|

Swallowing, nutrition and patient-rated functional outcomes at 6 months following two non-surgical treatments for T1–T3 oropharyngeal cancer

Abstract: Purpose: Altered fractionation radiotherapy with concomitant boost (AFRT-CB) may be considered an alternative treatment for patients not appropriate for chemoradiation (CRT). As functional outcomes following AFRT-CB have been minimally reported, this exploratory paper describes the outcomes of patients managed with AFRT-CB or CRT at 6 months post treatment.Methods: Using a cross-sectional analysis design, functional outcomes of 14 AFRT-CB and 17 CRT patients with T1-T3 oropharyngeal cancers were explored at 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Despite the small percentage of patients (7.2%) in our study who received 3D conformal treatment, we also found the use of 3D conformal RT techniques to be significantly associated with increased rates of g‐tube placement and prolonged tube dependence compared with the use of IMRT. Although radiotherapy intensification has been shown to improve locoregional control in patients with oropharyngeal cancer, the cost has been increased severity and duration of treatment‐related toxicity leading to increased g‐tube dependence . More conformal planning with IMRT that restricts the dose to pharyngeal musculature uninvolved with the tumor has been shown to reduce significant dysphagia and prolonged g‐tube dependence .…”
Section: Discussionmentioning
confidence: 99%
“…Despite the small percentage of patients (7.2%) in our study who received 3D conformal treatment, we also found the use of 3D conformal RT techniques to be significantly associated with increased rates of g‐tube placement and prolonged tube dependence compared with the use of IMRT. Although radiotherapy intensification has been shown to improve locoregional control in patients with oropharyngeal cancer, the cost has been increased severity and duration of treatment‐related toxicity leading to increased g‐tube dependence . More conformal planning with IMRT that restricts the dose to pharyngeal musculature uninvolved with the tumor has been shown to reduce significant dysphagia and prolonged g‐tube dependence .…”
Section: Discussionmentioning
confidence: 99%
“…It can lead to serious medical complications such as malnutrition, dehydration, and aspiration pneumonia, as well as decreased functioning, reduced participation in life activities, negative psychosocial consequences, and reduced quality of life (Cartmill et al . , McQuestion et al . , Nguyen et al .…”
Section: Introductionmentioning
confidence: 99%
“…Dysphagia, or difficulty swallowing, is a common acute and ongoing chronic effect of definitive, nonsurgical treatment for HNC. It can lead to serious medical complications such as malnutrition, dehydration, and aspiration pneumonia, as well as decreased functioning, reduced participation in life activities, negative psychosocial consequences, and reduced quality of life (Cartmill et al 2012, McQuestion et al 2011, Nguyen et al 2005, Nourissat et al 2012, Ottosson et al 2013. Speech and language therapists (SLTs) have an integral role in the diagnosis and management of dysphagia, and are core members of the multidisciplinary HNC team who provide services for people with dysphagia pre, during and post-treatment (Krisciunas et al 2012, Roe et al 2012.…”
Section: Introductionmentioning
confidence: 99%
“…The medical complications of dysphagia following head and neck cancer (HNC), including aspiration, malnutrition, and dehydration are now well recognised (Agarwal et al, 2011;Buchmann, Conlee, Hunt, Agarwal, & White, 2013;Cartmill, Cornwell, Ward, Davidson, & Porceddu, 2011bHutcheson & Lewin, 2012;Nguyen et al, 2008). As a consequence, in more recent literature there has been increased consideration of the functional outcomes and changes to quality of life (QoL) associated with dysphagia in the HNC population (Llewellyn, Weinman, McGurk, & Humphris, 2008;Lovell, Wong, Loh, Ngo, & Wilson, 2005;Nguyen et al, 2005).…”
Section: Introductionmentioning
confidence: 99%